Konsekuensi Perubahan Iklim pada Pertanian Lokal di Pakel Tulungagung terhadap Harga Pangan di Pasaran - Selvi Agustin; Nadya Putri Cantika; Mukhammad Nashrulloh; Nur Isroatul Khusna (STIKes Ibnu Sina Ajibarang, 2024)
Climate change has become a crucial issue affecting the agricultural sector worldwide, including in Pakel, Tulungagung. In this context, this research aims to investigate the consequences of climate change on local agriculture in Pakel, Tulungagung, particularly in relation to the prices of food in the market. Through in-depth analysis of relevant literature and data, this study identifies the impacts of climate change such as extreme weather fluctuations, increased uncertainty of harvest yields, and rising production costs. All these factors contribute to the rise in food prices in the local market. The findings of this research provide important insights for stakeholders, including the government, farmers, and consumers, to develop effective adaptation strategies and sustainable policies in addressing the challenges of climate change in the agricultural sector.